Incorporating basic needs to reconcile poverty and ecosystem services - Tomas Chaigneau; Sarah Coulthard; Katrina Brown; Tim M. Daw; Björn Schulte‐Herbrüggen (Conservation Biology, 2019)
Conservation managers frequently face the challenge of protecting and sustaining biodiversity without producing detrimental outcomes for (often poor) human populations that depend on ecosystem services for their well‐being. However, mutually beneficial solutions are often elusive and can mask trade‐offs and negative outcomes for people. To deal with such trade‐offs, ecological and social thresholds need to be identified to determine the acceptable solution space for conservation. Although human well‐being as a concept has recently gained prominence, conservationists still lack tools to evaluate how their actions affect it in a given context. We applied the theory of human needs to conservation by building on an extensive historical application of need approaches in international development. In an innovative participatory method that included focus groups and household surveys, we evaluated how human needs are met based on locally relevant thresholds. We then established connections between human needs and ecosystem services through key‐informant focus groups. We applied our method in coastal East Africa to identify households that would not be able to meet their basic needs and to uncover the role of ecosystem services in meeting these. This enabled us to identify how benefits derived from the environment were contributing to meeting basic needs and to consider potential repercussions that could arise through changes to ecosystem service provision. We suggest our approach can help conservationists and planners balance poverty alleviation and biodiversity protection and ensure conservation measures do not, at the very least, cause serious harm to individuals. We further argue it can be used as a basis for monitoring the impacts of conservation on multidimensional poverty.